Teaching and Assessing High-order Skills by Design and Technology Teachers in Botswana - Nenty, H. J.; Ngakaemang, K. M. (Advances in Social Sciences Research Journal, 2017)
Poor students’ performance in design and technology (D&T), especially at questions that call on high-order cognitive skills at national examinations, is symptomatic of teaching and assessment problems at classroom level. While it is accepted that this problem of poor performance could be multi-faceted, it is believed that a lasting solution can be found through the application of Bloom’s taxonomy of cognitive skills while preparing for and teaching in the classroom. Using a methodology orientated towards the quantitative paradigm within the post positivist philosophy and a validated questionnaire instrument, data was collected from 45 D&T teachers sampled purposively from 16 junior secondary schools in south eastern region of Botswana. Data analysis was done to test two related hypotheses and it was found that while D&T teachers teach to develop each of Bloom’s cognitive skill at a significant level, except generally for low-order skills, they were not able to do this when it came to assessment. These findings were discussed and relevant recommendations were drawn.